Textured Feminisms: Cairo, Tokyo, Beijing, 1907 - Booth, M (Duke University Press, 2015)
Comparing He-Yen Jhen’s work to that of her Egyptian contemporary Malak Hifni Nasif allows lateral thinking across Asian and African societies on how feminists articulated their stances with regard to male counterparts in their own societies, as well as the shifting gender-differential practices of the Euro/American societies that they critically evaluated. Can such comparisons elicit shared vocabularies—and parallel silences—that help us to situate feminisms historically as both cosmopolitan and deeply local interventions in times and places marked by late imperial capitalism?